Industrial Conflict and Industrial Relations in Italy : New Perspectives - Ramirez, Bruno (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
The author traces the changes which have occurred in Italy's industrial relations systems as a result of the great wave of strikes of 1969. Special emphasis is placed on the emergence of new structures of workers' representation at the plant level, and on the effect these have had on the method of negotiation.